Analysis of Genetic, Socio-economic, and Environmental Factors in Adolescent Mental Health: A Literature Review - Deviantony, Fitrio; Kaniya, Nurul; Zahro, Fatimatus; Lestari, Aynuning Hadi (Jurnal Kesehatan Komunitas Indonesia, 2024)
Background: A person's mental health plays a significant role in their lives since it allows them to function as living creatures and carry out their daily activities. A person in good mental health is able to see their own potential, manage everyday stressors, perform efficiently, and positively impact their surroundings. Aims: This study aims to analyze the relationship between genetic, socio-economic, and environmental factors on mental health in adolescents. Methods: A review of the literature from 2019 to 2024 was conducted as part of this research technique using Pubmed and Science Direct with the keywords “mental health”, “socio-economic factors”, “genetic factors”, “adolescents". Results: The literature review finds that mental disorders are caused by a combination of genetic, biological, psychological, and environmental factors. However, of the 15 factors that were examined, there was 1 factor that was not associated with adolescent mental health, namely physical activity. In a study conducted by Amir, et al. (2024) showed that there was no correlation between physical activity and anxiety (one of the mental health disorders). Conclusion: Based on the results of a literature review of 15 journals, it can be concluded that adolescent mental health is not only influenced by socio- economic factors but also by genetic, environmental, and interpersonal relationship factors.